Convergent ethical paradigms: a systematic review of islamic financial principles as a response to the challenges of the new world order - Joseph Hamonangan Sianipar; Maru Mary Jones Panjaitan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The new world order, marked by digital disruption, environmental crises, social inequality, and global governance changes, calls for a reconstruction of the ethical paradigm in the financial system. Islamic finance offers a foundation based on Maqāṣid al-Sharīʿah (Islamic Principles of Sharia), emphasizing justice, balance, social responsibility, and sustainability. This study aims to develop a convergent ethical paradigm through a systematic literature review (SLR) of Islamic financial principles addressing contemporary global economic challenges. Using the PRISMA 2020 guidelines, ten articles were selected, analyzed with thematic synthesis to identify key patterns. The results show that aligning Maqāṣid al-Sharīʿah with the Environmental, Social, and Governance (ESG) framework forms a strong ethical foundation for a sustainable financial system. Principles like distributive justice, transparency, and environmental preservation align with global sustainability goals. The study suggests that strengthening sharia governance, developing an ESG disclosure index, and integrating sharia-compliant fintech innovations are vital strategies to improve the credibility and accountability of Islamic finance. In conclusion, Islamic finance can establish a convergent ethical paradigm that upholds Sharia integrity while engaging with global sustainability standards, offering a conceptual framework for sustainable finance policies in the new world order.